STUDI EFISIENSI REAKTOR RAPID SAND FILTER DALAM PENURUNAN COD PADA AIR LIMBAH PENCUCIAN IKAN DI PASAR IKAN SIDOARJO - Oktavia, Lily; Khurin’ In (2477 - 6165, 2019)
The existence of many fisheries products is directly proportional to the number of existing fish markets, including the Sidoarjo Fish Market in the eastern ring area. The many activities in this fish market produce wastewater that must be considered for its management so as not to pollute the surrounding environment. These activities forexample from fish washing activities. The parameters of water used for washing fish are organic, with organic pollutants high enough, namely COD. The purpose of this study was to determine the reduction in levels of BOD (5,20) treatment of wastewater from fish washing from the Sidoarjo Fish Market using sedimentation tub reactors and Rapid Sand Filters (RSF). The research phase will be carried out using a laboratory scale using a Precipitating Body as a pretreatment and RSF as a secondary treatment. The research began with a preliminary test to determine the influent quality of fish washing water effluents, then pretreatment was conducted. RSF uses buffer media in the form of: zeolith and gravel Influent discharge effluents are varied in two variables 10 liters / dayand 15 liters / day. The processing results from the RSF were then analyzed by BOD parameters (5.20) for 4 consecutive days using the standard EPHA method. The results showed that treating fish washing wastewater using sedimentation tanks and RSF can reduce the content of organic pollutants through BOD parameters (5.20) with an effectiveness reaching an average of 90% with gravel media and 95% with zeolith media. So it can be concluded that the fish washing wastewater from the Sidoarjo fish market can be treated before being discharged into the river so that the BOD pollutant can be reduced up to 95% using RSF technology with zeolith media. Keywords: Fish Washing Liquid Waste, BOD, Rapid Sand Filter, Zeolith.